Self-constructed water-in-oil Pickering emulsions as a tool for increasing bioaccessibility of betulin - Chaoxi Zeng; Yuxian Wang; Yugang Liu; Shuxian Su; Yuting Lu; Si Qin; Meng Shi (Food Chemistry: X, 2024)
Self-constructed water-in-oil emulsions can be stabilized by a natural pentacyclic triterpenoid, betulin. A higher betulin concentration (3%) results in smaller emulsion droplet sizes. Microscopy, confocal laser scanning microscopy and rheology indicate that the stabilizing mechanism is attributed to betulin crystals on the emulsion interface and within the continuous phase, thereby enabling excellent freeze/thaw and thermal stability. The betulin Pickering emulsion (1%) significantly increased betulin bioaccessibility (22.4%) compared to betulin alone (0.2%) and betulin-oil physical mixture (7.9%). A higher level of betulin at 3% leads to smaller emulsion particle size, potentially resulting in a greater surface area. This, in return, promotes a higher release of free fatty acids (FFA), contributing to the release and solubilization of betulin from emulsions. Additionally, it leads to the formation of micelles, further increasing betulin bioaccessibility (29.3%). This study demonstrates Pickering emulsions solely stabilized by phytochemical betulin provides an innovative way to improve its bioaccessibility.